Eleanor Oliphant is Completely Fine - Honeyman, Gail (New York Pamela Dorman Books/Viking, 2017)
"Meet Eleanor Oliphant: she struggles with appropriate social skills and tends to say exactly what she's thinking. That, combined with her unusual appearance (scarred cheek, tendency to wear the same clothes year in, year out), means that Eleanor has become a creature of habit (to say the least) and a bit of a loner ... But everything changes when Eleanor meets Raymond, the bumbling and deeply unhygienic IT guy from her office"--
Keywords: Single women -- Fiction; Social isolation -- Fiction; Intergenerational relations -- Fiction; Friendship -- Fiction; Computer technicians -- Fiction; FICTION / Contemporary Women; FICTION / Literary; FICTION / Romance / Contemporary; Glasgow (Scotland) -- Fiction; Psychological fiction; Romance fiction